Bahan Ajar Daring Tata Bahasa bagi Pelajar BIPA 2 - Himmatun Ilmiah S; A. Syukur Ghazali; Nurchasanah Nurchasanah; Kusubakti Andajani (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Online teaching materials are urgently needed during a pandemic because of the limited distance to study directly to the destination country. Grammar material is one of the materials that must be taught, especially for beginner BIPA students. Therefore, the aim of this study was to produce teaching materials and online guides for BIPA 2 grammar. The development research model was adapted from Borg and Gall (1983). The results of the validation test and practitioner test state that this teaching material is feasible and needs to be revised and very feasible and does not need to be revised. The total results of the validation of BIPA material experts and practitioners were 84.8%, validation of learning technology was 95.5%, and limited field testing was 92.13%.Abstrak: Bahan ajar daring sangat dibutuhkan pada masa pandemi karena keterbatasan jarak untuk belajar langsung ke negara tujuan. Materi tata bahasa merupakan salah satu materi yang harus diajarkan, khususnya untuk pelajar BIPA tingkat pemula. Oleh karena itu, tujuan penlitian ini adalah menghasilkan bahan ajar dan panduan daring tata bahasa BIPA 2. Model penelitian pengembangan mengadaptasi dari Borg dan Gall (1983). Hasil uji validasi dan uji praktisi menyatakan bahwa bahan ajar ini layak dan perlu direvisi serta sangat layak dan tidak perlu direvisi. Hasil total validasi ahli materi BIPA dan praktisi 84.8%, validasi teknologi pembelajaran 95.5%, dan uji lapangan terbatas 92.13%.